Could kDNA-PCR in Peripheral Blood Replace the Examination of Bone Marrow for the Diagnosis of Visceral Leishmaniasis? - Natalia Souza de Godoy; Marcos Luiz Alves Andrino; Regina Maia de Souza; Erika Gakiya; Valdir Sabbaga Amato; José Ângelo Lauletta Lindoso; Lucia Maria Almeida Braz (Journal of Parasitology Research)
The aim of this study was to evaluate whether the molecular (kDNA-PCR) and parasitological diagnosis in peripheral blood (PB) could replace the invasive and painful bone marrow collection (BM) in the diagnosis of visceral leishmaniasis (VL). PB from suspected VL patients was evaluated by parasitological and molecular techniques using as the gold standard (GS) a combination of clinical, epidemiological, and immunochromatographic test (PB-rK39) results and parasitological examination of BM. Based on the GS, 38 samples from 32 patients were grouped: Group 1, 20 samples of VL cases, and Group 2, 18 samples of non-VL cases. In order to evaluate the parasitological and molecular techniques in PB, the samples were examined. From Group 1, PB kDNA-PCR was positive in 20 samples and in 19 of 20 in BM kDNA-PCR examination. However, the parasitological examination of buffy coat was insensitive, being able to detect only 4 cases from Group 1. All samples from Group 2 were negative. We concluded that, for the diagnosis of visceral leishmaniasis, the parasitological examination of peripheral blood was not useful; however, molecular diagnosis by kDNA-PCR, performed in peripheral blood, could be useful to replace the parasitological examination of bone marrow.